Water Hyacinth Extract in Herbal Medicine Development: Literature Review - Sayutri, Zelvisya; Rahmawati Safitri; Raodhatul Jannah; Rahma Azkiah; Julianti, Tri Budi (Universitas STRADA Indonesia, 2025)
Indonesia is a country with an extraordinary wealth of flora, one of which is water hyacinth (Eichhornia crassipes) which has been known as an invasive aquatic weed. Recent studies have shown this plant has potential as a raw material for herbal medicine. The purpose of this review is to evaluate the pharmacological activity and phytochemical content of water hyacinth based on current scientific literature. The method used was journal search and selection from 2021 to 2025 through PubMed, Google Scholar and ResearchGate databases with the keywords “Eichhornia crassipes”, ‘pharmacology’, and “bioactivity”. The results review showed water hyacinth extract has anti-inflammatory activity through decreasing proinflammatory cytokines, antidiabetic through activating SUR-1, GLP-1R, AMPK, and OCT-1 receptors and antibacterial against Prevotella intermedia and Staphylococcus aureus. In addition, anticancer activity was demonstrated through binding of active compounds to MCF-7 cancer cell receptors, as well as cytoprotective activity against oxidative stress in rat liver cells.